Stellung und Mitarbeit der Frau in der Gemeinde - Apolant, Jenny (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1910)
A carefully assembled synopsis of the available opportunities for women in public service work. The concentration is on Germany, but there is an overview of opportunities in other European countries as well.